Examining the Determinants of eBanking Adoption: Evidence from Nigeria - Tijjani Abdurrahaman, Daha; Sharubutu , Maimuna Saad; Sabiu, Tasiu Tijjani; Adam, Sa’adatu Balarabe; Ibrahim, Mohammed Gaddafi; Udu, Ama Aka (Technium Social Sciences Journal, 2021)
The trend of transacting in raw cash is giving way to electronic payment systems as a digital lifestyle is increasingly acceptable worldwide. In Nigeria, several empirical studies have investigated the determinants of Electronic Banking on urban bank customers. However, no study, to the best knowledge of the researcher captures the rural bank customers. This study fills this gap by examining the determinants of eBanking adoption in a rural area of Kano State, Nigeria. A survey design was employed and the data were collected through an electronic questionnaire distributed to a sample of 198 target respondents. Partial Least Structural equation modelling was employed in analyzing the hypothesized relationship based on a modified Technology Acceptance Model that introduces Trust and Quality of Internet Connection as suggested by extant literature. The study found that Perceived Usefulness was the construct that overwhelmingly influences Rural Bank Customers to adopt eBanking. It was further revealed that the Quality of Internet Connection is vital to Rural Bank Customers. In addition, the study highlights the importance of performance matrix analysis indicating the constructs that are performing well and those that need attention.